The role of electoral appeals in giving legitimacy to the general elections - a comparative study between Syria, Egypt and France - Addoum, Wissam Yosef; Arab, Walid Akel (Journal of Economic, Administrative and Legal Sciences, 2022)
This research aimed at clarify the role of electoral appeals in legitimizing the general elections in all its stages. The descriptive analytical approach and the comparative deductive approach were relied upon to reach the desired results, the most important of which are: 1- Electoral disputes and challenges arising from them are considered a tool to achieve the legitimacy of the general elections. 2- The electoral register is one of the foundations of the legality of the election. 3- The right to run for office is a right guaranteed to all citizens who meet the conditions specified by laws. Among the most important recommendations: 1- An accurate and comprehensive electoral appeals system should be developed that is characterized by simplicity and speed of decision making. 2- The Syrian legislator should follow in the footsteps of the Egyptian and French legislation in determining the right of others to challenge the voter register. 3- Building integrated and accurate systems for electoral appeals and adopting the successful experiences of some countries.